The Influence of Financial Literacy, Investment Experience, and Overconfidence on Investment Decisions in National University Master of Management Study Program Students with Risk Tolerance as an Intervening Variable - Dessy Yuliani; Andini Nurwulandari (International Journal of Social Service and Research, 2023)
This research uses a quantitative approach and Partial Least Square- Structural Equation Modeling (PLS-SEM) to test the relationship between the variables Financial Literacy (X1), Investment Experience (X2), Overconfidence (X3), Risk Tolerance (Z), and Investment Decisions ( Y) for National University Master of Management study program students. The results of descriptive statistical analysis reveal that Financial Literacy, Investment Experience, and Overconfidence have a positive and significant effect on Risk Tolerance, while Financial Literacy, Investment Experience, and Overconfidence have a positive effect on Investment Decisions. However, the results of the analysis show that Financial Literacy has an insignificant influence on Investment Decisions, while Investment Experience and Overconfidence have a positive and significant influence on Investment Decisions. Risk Tolerance also has a positive and significant effect on Investment Decisions. In addition, this research finds that Risk Tolerance mediates the relationship between Financial Literacy, Investment Experience, and Investment Decisions. In other words, the greater the Financial Literacy and Investment Experience, the Risk Tolerance will increase, which in turn will increase Investment Decisions. The results of this research provide important insights for National University Master of Management study program students and other stakeholders in understanding the factors that influence investment decisions, as well as the importance of understanding the level of financial literacy and investment experience in managing risk and making wise investment decisions.